Impact of blockchain technology on green supply chain practices: evidence from emerging economy - Mubarik, Mobashar; Raja Mohd Rasi, Raja Zuraidah; Mubarak, Muhammad Faraz; Ashraf, Rashid (Emerald Publishing Limited, 2021)
Purpose – This study investigates the impact of blockchain technology on green supply chain practices with the aim to promote pro-environmental settings in supply chains of manufacturing firms. Moreover, mediating role of environmental orientation is examined between blockchain technology and green supply chain practices. Also, moderating role of technological orientation in this connection is undertaken. Design/methodology/approach – The authors have applied a quantitative methodology in which a questionnairewas developed fromliterature.After that, data are collected from manufacturing firms ofMalaysia. The data collected are analysed by using PLS-SEM in which multiple regression and moderation are applied. Findings – The results of this study confirm the positive impact of blockchain on green supply chain practices. Also, the mediating role of environmental orientation is revealed in this relationship. Moreover, technological orientation is confirmed as a moderator which strengthens the relationship between blockchain technology and green supply chain practices. Research limitations/implications – This study has collected data from manufacturing firms of Malaysia. However, the authors have not undertaken service sector firms. Thus, they recommend future researchers to consider service sector firms in this context. Moreover, they have taken SMEs for this study and have neglected large firms. Therefore, in future, large firms could be taken to test the current study’s perspective in them. Furthermore, this study suggests to the policymaker and managers, especially of manufacturing concerns, to infuse Industry 4.0 technologies such as blockchain technology because of its manifold benefits. Practical implications – This study suggests to the policymaker and managers, especially of manufacturing concerns, to infuse Industry 4.0 technologies such as blockchain technology because of its manifold benefits. First, it will enhance the integration across the streams of the supply chain; secondly, it will improve the demand and supply planning which will eliminate the extra production and will enable firms to adopt just-in-time production by saving various costs associated otherwise. Importantly, these processes are against the pro-environmental behaviour which is pivotal to achieve green supply chain practices. Originality/value – This study contributes by joining the technological perspective of Industry 4.0 technologies and sustainability perspective of green supply chain in manufacturing concerns. In addition, the related concepts of technological orientation and environmental orientation are also undertaken to further adjoin the former fields. As a practical contribution, this study will, first, enhance the integration across the streams of supply chain; secondly it will improve the demand and supply planning which will eliminates the extra production and will enable firms to adopt just-in-time production by saving various costs associated otherwise. It is also suggested to instil pro-environmental behaviour or environmental orientation in the employees at all levels of firm. Moreover, technological orientation should also be improved by emphasizing on the importance of technology for environmentally friendly and green supply chain practices.